Student Diversity and Fulfilling The Target of The Differentiation Learning Curriculum - Berliana, Cindy; Fajarianto, Otto; Harsono, Yhonanda (IJESS International Journal of Education and Social Science, 2024)
It is very important for us as educators to know the diversity of students in the classroom to be able to determine differentiated learning models, approaches and strategies during learning. In this paper, we will discuss the diversity of students at SDN Lesanpuro 3 Malang with class IA research samples. From the physical diversity of students in class IA, there are 13 male students and 15 female students. In terms of sensory diversity, the majority have no obstacles. In terms of economic and demographic diversity, class IA students are very diverse, which is based on work factors. The majority of families and residences are in urban areas. Apart from that, judging from the learning outcomes of students in the fine arts learning content, line material also has quite satisfactory results. Based on the diversity of students in class IA, educators have implemented differentiated learning strategies in one aspect of the product in the fine arts learning content. The results of fulfilling the curriculum targets show that in fulfilling the curriculum targets at SDN Lesanpuro 3 class IA, the line material for fine arts learning content shows that students have been able to understand, identify, classify and create works regarding types of lines. And can also demonstrate concrete media TOURISM (Line Cards) individually.